Assessment of Colemanite Waste in Hybrid Fiber-Reinforced Mortars Exposed to Elevated Temperatures - Altun, Muhammet Gokhan; Benlioglu, Arif; Ozen, Suleyman (Springer Heidelberg, 2025)
This study systematically investigates the effects of colemanite waste and hybrid fibers on the high-temperature performance of cementitious mortars, aiming to mitigate the negative impact of colemanite waste on mechanical properties through the use of various fibers, both individually and in hybrid combinations, and thereby providing critical insights for sustainable construction materials. In the study, cement was used as the binder, with colemanite waste substituted at rates of 3, 5, and 7%. Standard sand was used as aggregate, and fibers were incorporated at a volume of 0.4% each of steel fiber, basalt fiber, polypropylene fiber, as well as hybrid fibers (0.2% steel + 0.2% basalt and 0.2% steel + 0.2% polypropylene). The compressive strength, flexural strength, and water absorption rates of the produced mixtures were determined at 7 and 28 days. Additionally, to assess the mechanical performance of the mixtures under high-temperature effects, the 28-day mixtures were exposed to temperatures of 300 and 600 degrees C, and residual compressive and flexural strengths were evaluated. The results indicate that the use of fibers, whether separately or in hybrid forms, enhances the mechanical properties, water absorption capacities, and high-temperature performance of the mixtures, regardless of the substitution ratio of colemanite waste. Among the mortars subjected to high temperatures, the sample containing 7% colemanite waste exhibited the lowest results, whereas the sample, which contained 3% colemanite waste and 0.4% steel fibers, yielded the best results.
Keywords: Colemanite waste; Fiber; Mortar; Elevated temperature; Sustainability